A Catalogue of Indian Euteliidae (Lepidoptera, Noctuoidea) - Joshi, Rahul; Singh, Navneet; Ahmad, Jalil; Farooqui, Shahabab A. (Zootaxa, 2024)
We present a catalogue of 104 valid species in 20 genera and two subfamilies i.e., Euteliinae and Stictopterinae of Indian Euteliidae, which represent 19.25% of the global Euteliidae (540 species). Out of 104 Indian species, Euteliinae are represented by 52 species in 14 genera and Stictopterinae by 52 species in six genera. Six new combinations are proposed and one old combination is revived. Taxonomic position of Mimanuga Warren, 1913 is discussed. For the included genera, type species and synonyms, if any, are given whereas for the catalogued species, type localities, synonyms, if any, distribution including Indian as well as global records are provided.